Progress Towards External Adjustment in the Euro Area Periphery and the Baltics - Kang, Joong (IMF Working Papers; Working Paper ;, 2014)
The euro area periphery countries and the Baltic countries, which had large current account deficits in the run-up to the crisis, needed adjustment of relative prices to achieve both internal and external balances. Thus far, tangible progress has been made through lower wages and/or higher productivity relative to trading partners ('internal devaluation'), which contributed to narrowing current account deficits and shifting output towards the tradables sector. While some early adjusters cut wages more rapidly followed by productivity improvement, others have only slowly improved productivity largely through labor shedding. This adjustment for most countries has come along with a substantial recession as the unit labor cost improvement has largely come from falling employment and much of the current account improvement from import compression. Going forward, these countries still need to generate growing tradables sector employment and to continue adjustment to prevent imbalances from returning as output gaps close.